Using Google Bard as an Al-Powered Chatbot Tool for Writing English Essays - Fitria, Tira Nur (Institut Teknologi Bisnis AAS Indonesia, 2024)
This research describes the use of Google Bard as an Al-Powered Chatbot Tool for writing English essays. This research is descriptive qualitative. The analysis shows that Bard is an Al-powered chatbot tool designed by Google to simulate human conversations using natural language processing and machine learning. Besides supplementing Google search, Bard can be integrated into websites, messaging platforms, or applications to provide realistic, natural language responses to user questions. Users can collaborate with Bard to brainstorm ideas, spark creativity, and accelerate writing productivity. Several ways to use Google Bard are: Visit the official website https://Bard.google.com or https://Bard.google.com/chat and make sure that we have logged in to our Google account. A chat room of Bard will open. Type and send prompts (commands/questions). Bard will read the prompts and present the responses. Bard has alternative answer drafts based on the criteria we want. Click on one of the three drafts that fit our criteria. The researcher does several trials using Bards. The view shows “Hi, I’m Bard. Tell me what’s on your mind, or pick a suggestion. I have limitations and won’t always get it right, but your feedback will help me improve”. The researcher asks “Hallo, good afternoon. Can you help me to do my English assignment?”, then Bard answer “Bard answers “Yes, I can help you to do your English assignment”, then adds several tips for writing an essay and mentions specific types of assignments i.e essays, research papers, and creative writing assignments. The researcher asks Bard specifically “Can you write English an essay which consists of 1 paragraph about